Krwotok poporodowy - przyczyny, objawy, postępowanie przedszpitalne = Postpartum hemorrhage - causes, symptoms, prehospital treatment - Magdalena Sowa; Michał Tarkowski; Kamil Wójcik; Andrzej Winnicki; Łukasz Saletnik (Kazimierz Wielki University, 2015)
Sowa Magdalena, Tarkowski Michał, Wójcik Kamil, Winnicki Andrzej, Saletnik Łukasz. Krwotok poporodowy - przyczyny, objawy, postępowanie przedszpitalne = Postpartum hemorrhage - causes, symptoms, prehospital treatment. Journal of Education, Health and Sport. 2015;5(4):319-324. ISSN 2391-8306. DOI: 10.5281/zenodo.17155 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%284%29%3A319-324 https://pbn.nauka.gov.pl/works/555244 http://dx.doi.org/10.5281/zenodo.17155 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.03.2015. Accepted: 10.04.2015.   Krwotok poporodowy - przyczyny, objawy, postępowanie przedszpitalne Postpartum hemorrhage - causes, symptoms, prehospital treatment   Magdalena Sowa1, Michał Tarkowski2, Kamil Wójcik2, Andrzej Winnicki3, Łukasz Saletnik1   1Katedra i Zakład Laseroterapii i Fizjoterapii,  Uniwersytet Mikołaja Kopernika w Toruniu 2Wojewódzka Stacja Pogotowia Ratunkowego w Bydgoszczy 3Katedra Technologii Postaci Leku, Uniwersytet Mikołaja Kopernika w Toruniu   Adres do korespondencji: Magdalena Sowa Katedra i Zakład Laseroterapii i Fizjoterapii Uniwersytet Mikołaja Kopernika w Toruniu Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy ul. Marii Skłodowskiej - Curie 9 85 - 094 Bydgoszcz e - mail magdalena.sowa@cm.umk.pl   Streszczenie Krwotok poporodowy stanowi stan zagrożenia życia. Jest najczęstszą przyczyną zgonów wśród położnic w okresie okołoporodowym. Wczesna identyfikacja czynników ryzyka oraz znajomość algorytmów postępowania pozwala zredukować kliniczne następstwa hipowolemii oraz zachować funkcje rozrodcze pacjentki. W pierwszej kolejności wdraża się metody leczenia zachowawczego.   Słowa kluczowe: krwotok poporodowy, objawy kliniczne, postępowanie ratunkowe.       Abstract Postpartum hemorrhage is a life-threatening condition. It's the most common cause of death among parturient women in the perinatal period. Early identification of risk factors and the knowledge regarding the algorithms of conduct allow for reduction of the clinical consequences of hypovolemia and for preserving patient's reproductive functions. In the first place, the methods of conservative treatment are implemented.   Key words: postpartum hemorrhage, clinical symptoms, rescue procedure.